The Sexual Dimorphic Synapse: From Spine Density to Molecular Composition - Uhl, Mara; Schmeisser, Michael J.; Schumann, Sven (Frontiers in Molecular Neuroscience, 2022)
A synaptic sexual dimorphism is relevant in the context of multiple neurodevelopmental, neurodegenerative, and neuropsychiatric disorders. Many of these disorders show a different prevalence and progression in woman and man. A similar variance is also present in corresponding animal models. To understand and characterize this dimorphism in pathologies it is important to first understand sex differences in unaffected individuals. Therefore, sexual differences have been studied since 1788, first focusing on brain weight, size, and volume. But as these measures are not directly related to brain function the investigation of sexual dimorphism also expanded to other organizational levels of the brain. This review is focused on sexual dimorphism at the synaptic level as these specialized structures are the smallest functional units of the brain, determining cell communication, connectivity, and plasticity. Multiple differences between males and females can be found on the levels of spine density, synaptic morphology, and molecular synapse composition. These differences support the importance of sex disaggregated data. The specificity of changes to a particular brain region or circuit might support the idea of a mosaic brain, in which each tile individually lies on a continuum from masculinization to feminization. Moreover, synapses can be seen as the smallest tiles of the mosaic determining the classification of larger areas.